Legislation on the protection of experimental animals - Ornik, Dragica (Radiology and oncology (Ljubljana), 2001)
The aim of this paper is to establish the current situation in the field of legislation on the protection of experimental animals in Slovenia. The protection of experimental animals has been regulated by the provisions of theProtection of Animals Act.1 On the basis of this act, the Instructions on Conditions for the Issuing of Authorisations for Experiments on Animals for Scientific and Research Purposes2 and the Rules on the Ethics Commission for Experiments on Animals 3 have been used. The basic protection of experimental animals is provided for by a system of permits for experiments on animals. Permits for experiments on animals are granted by the administrative authorities responsible for veterinary medicine in cases where experiments areurgently required for medical, veterinary medical, or scientific and research purposes and the results are expected to produce important new knowledge, or when the suffering of animals is ethically acceptable in comparison with what the experiment is expected to achieve; where, in cases ofbasic research, experimental aims cannot be achieved by any other method or procedure, the experiment is performed on the minimum possible number of animals of the lowest neurophysiological sensitivity and a method is used thatcauses the minimum level of suffering, pain or lasting harm. Staff involved in the execution of experiments or in the care and nursing of animals, the premises for the accommodation or rearing and provision of animals, and the installations and devices used must all comply with the set conditions. (Abstract truncated at 2000 characters)
Keywords: Animal husbandry; Animal rights; Animals, laboratory; poskusne živali; zakonodaja; zaščita živali; živali; Živali laboratorijske; Živali, zaščita; Živinoreja